Modeling options markets by focusing on active traders - Qiu, G. (2013)
In this work, we study the complex behavior of options markets characterized by the volatility smile phenomenon, through microsimulation (MS). We adopt two types of active traders in our MS model: speculators and arbitrageurs, and call and put options on one underlying asset. Speculators make decisions based on their expectations of the asset price at the option expiration time. Arbitrageurs trade at dierent arbitrage opportunities such as violation of put-call parity. Dierence in liquidity among options is also included. Notwithstanding its simplicity, our model can generate implied volatility (IV) curves similar to empirical observations. Our results suggest that the volatility smile is related to the competing eect of heterogeneous trading behavior and the impact of dierential liquidity.